PENGGUNAAN MEDIA PUISI DAN PENDEKATAN SAVI UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN SISWA KELAS VI SEKOLAH DASAR - Cerianing Putri Pratiwi (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
This study aims to improve quality of learning process through using write short andimprove students' ability through to write short stories using poetry media and SAVIapproach. Subjects in this study is students of class VI SDN Tanjung 3. Research objectof learning to write short stories in Indonesian Language. Data collection techniquesused in this study consist of (a) observation, (b)interview, (c)study of document,(d)questionnaire, (e)tasks. Testing the validity of data is done by triangulation.Approaches of analysing data which used in this research are descriptive qualitative anddescriptive comparative. The conclusions of this research can be known that the media ofpoetry and SAVI approach can improve quality in learning process and ability to writeshort stories in Class VI SDN Tanjung 3. From the results of the pre-action learningprocess is still less than optimal and the average ability to write short stories 65.8. Thefirst cycle, which is when the learning process students are more enthusiastic andaverage ability to write is 75.5. In second cycle, the quality of learning process has moreincreased. The average student's ability to write short stories was increased until 82.8.Keywords: writing short stories, SAVI approach, poetry media